Применение полуэмпирических методов определения акустических нагрузок к оценке нагружения отсеков ракетоносителей - Аврамов, К. В.; Батутина, Т. Я.; Бондарь, Д. С.; Мартыненко, Геннадий Юрьевич; Шеремет, И. В.; Мартыненко, В. Г. (Київський політехнічний інститут ім. Ігоря Сікорського, 2017)
Запропоновано підхід для розрахунку спектральних густин турбулентних пульсацій тисків, заснований на чисельному моделюванні обтікання ракети в'язким газовим потоком, і застосування емпіричних залежностей для розрахунку спектральних густин пульсацій. В результаті застосування цієї методики досліджуються спектральні густини турбулентних пульсацій та визначаються акустичні навантаження на корпус ракетоносія при його русі з надзвуковою швидкістю.

The problem of sound spectra evaluation around the bays of an LV during the supersound flight is considered in the article. In order to perform the evaluation four different evaluation methods of pressure pulsations spectral density proposed by Efimtsev, Laganelli, Robertson and Chase-Howe are used. After the sound power spectra calculated by each of four evaluation methods have been compared with the measured sound power values on the real LV, the Chase-Howe method has been chosen as the most accurate one in the matter of describing the actual physical processes. The initial data for the calculation of sound power spectra have been obtained from the results of finite-element modeling of super-sound flow around the fairing, performed in the Ansys 17.0. (Fluent module).
Keywords: обтекатель ракетоносителя; турбулентные пульсации; ракета; эргодичность; спектральная плотность; пограничный слой; сверхзвуковой газовый поток